The role of communication variables in influencing job retention of Filipino call center agents in Metro Manila and Region 6 - Jamandre, Niel Kenneth
"... zeroes in on the communicative struggles in the call center industry, currently the nation's answer to mass unemployment. After discussing the talent saturation experienced by call centers in Manila, he moves on to analyze the various communication factors that influence the decision of Filipino call center agents ... to continue working for their companies, and then compares the job retention factors in Metro Manila with those of Region 6, which has become another favoured region for Business Process Outsourcing companies." -- Introduction
Keywords: Business process outsourcing (BPO).; Employee retention; Communication in personnel management; Organizational socialization; Labor economics